AGRITOURISM AS A CATALYST FOR SUSTAINABLE RURAL DEVELOPMENT: A LITERATURE REVIEW - Davidović, Jovana; Pantović, Danijela; Mićović, Andrej (The European Journal of Applied Economics, 2025)
Agritourism plays a crucial role in promoting sustainable development in rural areas by integrating tourism with agricultural practices. This form of rural tourism not only supports the preservation of natural and cultural heritage but also fosters economic growth and social cohesion in communities often affected by depopulation and economic decline. Sustainable practices within agritourism, such as organic farming, energy efficiency, and eco-friendly activities, further enhance its viability as a development strategy. This paper reviews existing literature on agritourism as a key strategy for sustainable rural development, with a particular focus on its potential application in the Republic of Serbia. Furthermore, significant and relevant data from statistical databases in the country are presented, shedding light on the current state of agritourism development. The paper emphasizes the importance of effectively managing sustainable agritourism development and proposes key research questions for further exploration. These questions aim to enhance understanding of sustainable agritourism in the Republic of Serbia. By synthesizing existing findings, the paper also highlights the need for continued research in this field to inform decision-making and develop effective strategies for rural development.